Leaf area index and SPAD during the soybean development cycle at different plant densities and their relation to grain yield - Yokoyama, Anderson Hideo (2018)
Sowing density in the soybean crop promotes several morphophysiological changes in the plants, which can alter plant growth and grain yield. The objective of this study was to evaluate the effect of soybean plant densities on the leaf area index (LAI) and Soil Plant Analysis Development (SPAD) index during the soybean crop development cycle and correlating these data with grain yield. The experiment was conducted in the experimental area of Embrapa Soja, Londrina, Paraná State, Brazil, under a randomized complete block design, with five replications. The densities of 120, 230, 340 and 380 thousand viable plants ha-1 were evaluated in row spacing of 0.45 m using the BRS 359 RR cultivar, which has indeterminate growth type and compact architecture. The increased plant density promotes an increment in LAI from the V4 stage to R3; however, after this stage, LAI is similar among densities. Plant density did not change the SPAD index before R5.4. During the vegetative growth there is no correlation between LAI and SPAD and grain yield, but in the grain filling period there are positive correlations between these variables.